2015
DOI: 10.1155/2015/321528
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Finite Element Analysis of Anterior Single Implant‐Supported Prostheses with Different Bone Anchorages

Abstract: The aim of this study was to evaluate the stress distribution of monocortical and bicortical implant placement of external hexagon connection in the anterior region of the maxilla by 3D finite element analysis (FEA). 3D models were simulated to represent a bone block of anterior region of the maxilla containing an implant (4.0 × 10.0 mm) and an implant-supported cemented metalloceramic crown of the central incisor. Different techniques were tested (monocortical, bicortical, and bicortical associated with nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
5
21
0
4
Order By: Relevance
“…Due to the significant advancement in computer science, there has been a remarkable progress in numerical simulations. In the field of dentistry, these simulations have been mostly performed for stress analysis using finite element method [14][15][16]. Computational fluid dynamics (CFD) is widely used to simulate fluid flow which cannot be experimentally reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant advancement in computer science, there has been a remarkable progress in numerical simulations. In the field of dentistry, these simulations have been mostly performed for stress analysis using finite element method [14][15][16]. Computational fluid dynamics (CFD) is widely used to simulate fluid flow which cannot be experimentally reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…O método dos elementos finitos tem sido extensivamente utilizado como ferramenta de análise mecânica na odontologia 9,[12][13][14][22][23][24][25] , porém, como qualquer técnica de pesquisa, apresenta limitações inerentes ao método, às simplificações impostas ao ambiente da análise e ao modelo 6 . A interpretação dos resultados quantitativos apresenta a distribuição de forças dentro do implante.…”
Section: Discussionunclassified
“…Resultados: as tensões de von Mises máximas (MPa) nos modelos do implante cone morse (CM) e do tecido ósseo do tipo paralelepípedo foram de 14.30 tativa de resultados positivos, existem fatores que podem influenciar no desempenho do tratamento com implantes. A transmissão da carga pelo implante e a distribuição das tensões no tecido ósseo representam fatores significativos na determinação do sucesso ou da falha do sistema [5][6][7][8][9] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…According to studies, it can be stated that in low-quality bone tissues, stress concentration and deformation are substantially higher. It is also found that the use of bicortical techniques with the insertion of longer implants decreases stress distribution in neighbouring bone tissue, and also decreases the tendency of deformation [9].…”
Section: Research History: Titanium As An Implant Materials and Mechanmentioning
confidence: 97%